Predicting adherence to antiretroviral therapy and retention to HIV care : effects of baseline biopsychosocial status and neuropsychological functioning - Mark, Daniella (Department of Psychology, 2015)
These drugs have demonstrated efficacy in improving immune function and reducing HIV-related morbidity and mortality, and while a cure is not available, patients on treatment may live longer, healthier lives. However, early optimism has been tempered by the growing recognition that meticulous adherence is a prerequisite for optimal clinical response and prevention of drug resistance.